2006
DOI: 10.1111/j.1471-0528.2006.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterotubal transport disorder in adenomyosis and endometriosis—a cause for infertility

Abstract: Objective  Uterine hyperperistalsis and dysperistalsis are common phenomena in endometriosis and may be responsible for reduced fertility in cases of minimal or mild extent of disease. Since a high prevalence of adenomyosis uteri has been well documented in association with endometriosis, we designed a study to examine whether hyperperistalsis and dysperistalsis are caused by the endometriosis itself or by the adenomyotic component of the disease. Design  A prospective observational study. Setting  University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 28 publications
2
74
2
4
Order By: Relevance
“…Potentially, the presence of adenomyosis may have a role, with evidence showing reduced fertility in baboons with adenomyosis [ 38 ]. Human studies point to a similar association between adenomyosis and subfertility [ 39 ] with an effect on uterine peristalsis and sperm transport [ 40 ] as well as a higher rate of implantation failure with ART [ 41 ]. Adenomyosis and endometriosis have a clinical correlation with the more advanced stages of endometriosis [ 42 ].…”
Section: Adenomyosis and Infertilitymentioning
confidence: 94%
“…Potentially, the presence of adenomyosis may have a role, with evidence showing reduced fertility in baboons with adenomyosis [ 38 ]. Human studies point to a similar association between adenomyosis and subfertility [ 39 ] with an effect on uterine peristalsis and sperm transport [ 40 ] as well as a higher rate of implantation failure with ART [ 41 ]. Adenomyosis and endometriosis have a clinical correlation with the more advanced stages of endometriosis [ 42 ].…”
Section: Adenomyosis and Infertilitymentioning
confidence: 94%
“…Using a 99 Tclabeled macroalbumin aggregates in a procedure referred as hysterosalpingo scintigraphy, Kissler and colleagues reported evidence of retrograde transport alterations in endometriosis and adenomyosis. 472,473 This approach is cumbersome, however, and does not lend itself to repeated measurements, nor to studies conducted in mock reproductive conditions. An advantage of HySo over x-ray-based methods for assessing tubal function is the possibility of repeating examinations.…”
Section: Infusion Sonographymentioning
confidence: 99%
“…27 In a provocative series of publications, Leyendecker's team promoted the concept that endometriosis is associated with a hyperkinetic-dyskinetic condition of the uterus 473 which impairs the retrograde transport of sperm during the follicular phase, 24,231,540 and the proper antegrade emptying of uterine content at the time of menses. 236 From their studies using the uterine displacement of 99 Tc-labeled MAA, these authors observed two pathological findings in endometriosis: (1) a pathological increase in retrograde transport at the time of menses; and (2) the loss of retrograde transport targeted toward the tube that faces the developing follicle during the late follicular phase of natural cycles.…”
Section: Endometriosis and Uterine Contractilitymentioning
confidence: 99%
“…Kissler et al in 2006 [4] reported that endometriosis leads to a significant restriction in uterotubal transport capacity. They concluded that impeded hyperperistalsis and dysperistalsis in uterotubal transport associated with endometriosis may be the reason of infertility in these women [4]. Severe endometriosis is also associated with pelvic adhesions and a distortion of pelvic anatomy leading to a possible mechanic or anatomic disturbance of fertility [5,6].…”
Section: Endometriosis and The Alterations In Pelvic Anatomymentioning
confidence: 99%